Is hard Brexit detrimental to EU integration? Theory and evidence - Mikolajun, Irena; Viaene, Jean-Marie (Munich, 2018)
"In the struggle between the forces of free trade and the restrictive influence of insularism the latter recently seems to have the upper hand. This is illustrated by the referendum of June 23, 2016 where the United Kingdom (UK) voted to leave the European Union (EU). In this paper we evaluate the consequences of this event for EU integration. In particular, we analyze how the extent of EU economic integration would change once the UK leaves the Union. To that end we develop an integration benchmark that consists of the steady state production equilibrium characterized by arbitrage pricing and perfect factor mobility. We apply metrics to measure the distance between this benchmark and the data. We find that the integration in the EU is incomplete and its trend is non-linear while Brexit would not bring negative consequences to its development.."